Vapor compression air conditioning system with solar heat collector - A. K. Al-Okbi; Yu. V. Vankov (Известия высших учебных заведений: Проблемы энергетики)
THE RELEVANCE of the study lies in the fact that air conditioning systems in Iraq consume more than half of the electricity generation. During the summer, when temperatures rise,  the  demand  for  air  conditioning  increases,  resulting  in  constant  power  outages. Consumers  are  starting  to  use  local  generation -  diesel  generators,  which  increase environmental pollution. THE PURPOSE. Consider the problems thermal energy from the sun is  an  ideal  solution  for  reducing  electricity  consumption,  increasing  the  performance  of  air conditioners,  ensuring  continuity  of  power  supply  and  reducing  pollution  from  diesel generators and power plants, as well as saving energy and reducing the consumption of fossil fuels.  METHODS.  When  solving  the  problem,  a  comparison  of  options  for  standard  and (hybrid  using  solar  thermal  energy)  air  conditioning  systems  was  used.  In  a  hybrid  system, thermal energy enters the system from a solar collector built behind the compressor. Thermal parameters  and  level  of  electricity  consumption  were  calculated.  RESULTS.  The  article showed that a hybrid air conditioning system using solar thermal energy is more efficient than a  traditional  system,  as  it  increases  the  cooling  coefficient  by  (38.9 - 46.3%)  and  reduces electricity  consumption  by  (56.89 -  66.66).  %).  CONCLUSION.  The  use  of  a  hybrid  air conditioning system in the climate of Baghdad city with a vapor compression air conditioning system  reduced  the  electrical  energy  consumption  of  the  compressor  and  increased  the performance  of  the  system,  which  will  lead  to  increased  reliability  of  power  supply  and eliminate the need to use local diesel generators.